Step 1: Differentiating the given equation.
The given equation is:
\[
x^y + y^x = a^b
\]
Let \( u = x^y \) and \( v = y^x \). Differentiating \( u \) and \( v \) with respect to \( x \), we have:
\[
u = x^y \quad \Rightarrow \quad \frac{du}{dx} = x^{y-1}y + x^y \log x \cdot \frac{dy}{dx}
\]
\[
v = y^x \quad \Rightarrow \quad \frac{dv}{dx} = y^x \cdot \log y \cdot \frac{dy}{dx} + y^{x-1}
\]
Step 2: Differentiating the equation.
Differentiating both sides of \( u + v = a^b \) with respect to \( x \), we get:
\[
\frac{du}{dx} + \frac{dv}{dx} = 0
\]
Substituting the values of \( \frac{du}{dx} \) and \( \frac{dv}{dx} \), we obtain:
\[
x^{y-1}y + x^y \log x \cdot \frac{dy}{dx} + y^x \log y \cdot \frac{dy}{dx} + y^{x-1} = 0
\]
Step 3: Simplifying the equation.
Grouping terms involving \( \frac{dy}{dx} \), we get:
\[
x^y \log x \cdot \frac{dy}{dx} + y^x \log y \cdot \frac{dy}{dx} = -x^{y-1}y - y^{x-1}
\]
Factoring out \( \frac{dy}{dx} \):
\[
\frac{dy}{dx} \left( x^y \log x + y^x \log y \right) = -\left( x^{y-1}y + y^{x-1} \right)
\]
Step 4: Solving for \( \frac{dy}{dx} \).
\[
\frac{dy}{dx} = \frac{-\left( x^{y-1}y + y^{x-1} \right)}{x^y \log x + y^x \log y}
\]
Conclusion:
The derivative \( \frac{dy}{dx} \) is:
\[
\frac{dy}{dx} = \frac{-\left( x^{y-1}y + y^{x-1} \right)}{x^y \log x + y^x \log y}.
\]